1663c Agrichemical exposure in australian farmers – monitoring, measuring and making a difference. (24th April 2018) - Brumby, Susan; Cotton, Jacquie; Phillips, Tam; Russell-Green, Sienna; Edwards, John
Abstract : Exposure to organophosphates at low levels over time has been associated with neurological conditions. In-field Personalised Cholinesterase Assessment Project (PCAP) is identifying the effect on cholinesterase (ChE) inhibition in Victorian (Australia) farmers caused by the application of organophosphates (OPs) and ChE inhibiting insecticides. Accurate field assessment is particularly important for remote rural communities and current available measurement does not accurately estimate individual risk. Funded by the Shepherd Foundation and commencing in April 2016 this work trials an innovative, transportable assessment tool, identifying farmers with reduced ChE activity, who are at risk of neurological symptoms and/or unknown chronic low level exposure. Using oxime regeneration to stimulate recovery ChE in vitro —a more accurate and meaningful estimate of the percentage inhibition of cholinesterase—is generated for the farmer. This new approach will provide farmers with instant results from a measurement tool using their own ChE inhibition range. Validated across 10 time points in 5 Victorian farming locations, the study involves 61 farmers and agricultural workers (crop and/or livestock) aged between 20–75 years. This presentation will discuss the results generated using this novel, objective and portable field test including post participation behavioural changes. This research is providing farmers with fast evidence of personal exposure through individual results. This is leading to practice change, attitude shift, prevention of further exposures and possible reduction or change of pesticide use.